2018
DOI: 10.1093/pch/pxy070
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly training objectives and requirements for paediatric residents in Canada

Abstract: In the absence of national standards for scholarly requirements, paediatric resident training varies significantly across Canadian programs. This variability may contribute to significant differences in trainee experiences and productivity. A panel of coordinators of paediatric resident research programs from across Canada met in 2014, to share experiences and identify barriers to successful resident scholarly activity. A survey of all programs was completed in 2015. A scoping review and series of meetings led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…We were also pleased to note increased scholarly activity with ASK, as reported with comparable rotations[9,24,27]. Previously, the most frequently identified major barrier to completing a scholarly project was lack of time[15,30]. However, the lack of a research curriculum, statistical support, and funding have also been identified[30].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We were also pleased to note increased scholarly activity with ASK, as reported with comparable rotations[9,24,27]. Previously, the most frequently identified major barrier to completing a scholarly project was lack of time[15,30]. However, the lack of a research curriculum, statistical support, and funding have also been identified[30].…”
Section: Discussionmentioning
confidence: 94%
“…Our curriculum was structured using the 6 steps of Kern [13] Step 1: Problem identification and general needs assessment The senior author is a member of the Canadian Pediatric Resident Research group; bi-annual meetings are held with the Canadian Paediatric Society to share strategies to enhance scholarly and academic activities [14,15]. An extensive literature search was conducted, and contacts were made with other training programs to share curricula, which largely focussed on scholarly activities rather than the range of academic skills we wished to highlight.…”
Section: Curriculum Developmentmentioning
confidence: 99%
“…It is not known which is the best among the various reported methods on how to promote scholarly activities in residency programs 7,9,12–21 . Some studies concluded that “a scholarly culture is most important” to promote scholarly activities 8,16 and the JPS reform of the publication requirement policy in 2017 can be said to act at least as a compelling force, so to speak, to promote a scholarly culture.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known which is the best among the various reported methods on how to promote scholarly activities in residency programs. 7,9,[12][13][14][15][16][17][18][19][20][21] Some studies concluded that "a scholarly culture is most important" to promote scholarly activities 8,16 and the JPS reform of the publication requirement policy in 2017 can be said to act at least as a compelling force, so to speak, to promote a scholarly culture. It has been reported from Japan and other countries that conference presentations do not always lead to publications, 11,17,19,20 so the results of this study showing that publications increased while presentations did not, and that not only case reports but also original articles increased, may indicate a growing scholarly culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation